(untitled) (Revista Argentina de Cirugía, 2021)
Background: Frantz tumors, or solid pseudopapillary neoplasm of the pancreas (TSP) are rare pancreatic neoplasms, commonly diagnosed in young women. They are often asymptomatic, and despite their malignant potential, the prognosis is good after resective surgery. Objective: The aim of this article is to describe four cases in our hospital, and make a review of literature on the subject. Materials and methods: retrospective and observational study of the cases diagnosed and treated in the H.C.FF.AA (Montevideo, Uruguay), from 2007 to 2015. We analyzed epidemiologic characteristics, clinical presentation, tumor localization, surgical morbidity and mortality, durantion of surgery, hospital stay and follow up. Results: we found four cases, in young female, mean age 18 years at presentation (range 16 to 24 years), average tumor size 9.5 cm (range 4 to 20 cm), and the clinical findings were abdominal pain and an enlarged abdominal mass (in 3 of 4 cases), tumor localization in